2003
DOI: 10.1007/s00277-002-0591-z
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B-cell lymphoma arising from donor lymphoid cells after renal and pancreatic transplantation

Abstract: A patient with both a renal and pancreatic transplantation developed a diffuse large B-cell lymphoma, Epstein-Barr virus-related, 14 months after the surgical procedure. Tumor was confined to the transplanted organs: head of the pancreas and hilar lymph node of the transplanted kidney. Chimerism analysis demonstrated the tumor origin from donor lymphoid cells. Immunosuppression was discontinued and chemotherapy with cyclophosphamide, hydroxydaunomycin, vincristine, and prednisone (CHOP) was started. However, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 12 publications
4
5
0
Order By: Relevance
“…He received CHOP without success, similar to our patient the allografts were removed, rituximab was administered in the described case after transplantectomy and the patient also remained in complete remission (14). There is one further case report about a SPKT patient with lymphoma of donor origin in both kidney and pancreas allografts, who in contrast to our patient presented without symptoms and was diagnosed by routine ultrasound examination.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…He received CHOP without success, similar to our patient the allografts were removed, rituximab was administered in the described case after transplantectomy and the patient also remained in complete remission (14). There is one further case report about a SPKT patient with lymphoma of donor origin in both kidney and pancreas allografts, who in contrast to our patient presented without symptoms and was diagnosed by routine ultrasound examination.…”
Section: Discussionsupporting
confidence: 65%
“…However, in SPKT as shown in our patient and the case described by Cibeira et al (14), explantation of the allografted organs after chemotherapy is a curative treatment option. As the origin of the lymphoma influences prognosis and further therapy in addition to histopathological evaluation microsatellite analysis should be performed.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…From the histological point of view, a spectrum of lesions ranging from infectious mononucleosis to a malignant lymphoma comprises the clinical entity known as PTLD (9). A number of small‐scale studies and case reports have shown that PTLDs localized in the graft organ itself may originate from donor cells without being donor transmitted (10–31). Nevertheless, contrary to bone marrow transplant where PTLDs typically derive from donor lymphocytes, the majority of PTLDs that develop after organ transplantation derive from recipient lymphocytes (32–34).…”
Section: Introductionmentioning
confidence: 99%